Exploring Public Sentiments on Halal Food: A Social Network Analysis - Nasya Tanasya; Muhamad Subhi Apriantoro (Universitas Muhammadiyah Surakarta, 2025)
Purpose: This study aims to analyze public sentiment and discourse regarding halal food by utilizing social media analysis to understand how public perceptions and interest in halal food are formed and influenced. Methodology: The study employs a social media analytics approach grounded in social studies theory. Data were collected from multiple social media platforms between September 5 and September 11, 2024, using the Talkwalker Social Intelligence Platform. The analysis includes monitoring public opinion trends, thematic analysis of recurring discourse themes, and the application of Social Network Analysis (SNA) to examine interaction patterns. Results: The findings reveal significant trends in public reactions to halal food, including notable shifts in perceptions of key issues. The results highlight increasing global awareness of halal food and demonstrate the influential role of social media in shaping public opinion and disseminating halal-related information. Applications/Originality/Value: This study contributes original insights to the literature on halal studies and social research by demonstrating the effectiveness of social media analysis and SNA in capturing public sentiment. The findings provide practical implications for policymakers, halal industry stakeholders, and researchers in developing effective communication strategies and enhancing public understanding of halal food within contemporary social contexts.